Long Non-Coding RNAs Play a Role in the Pathogenesis of Psoriatic Arthritis by Regulating MicroRNAs and Genes Involved in Inflammation and Metabolic Syndrome - Dolcino, Marzia; Pelosi, Andrea; Fiore, Piera Filomena; Patuzzo, Giuseppe; Tinazzi, Elisa; Lunardi, Claudio; Puccetti, Antonio (Frontiers in Immunology, 2018)
Psoriatic arthritis (PsA) is an inflammatory arthritis, characterised by inflammation of entheses and synovium, leading to joint erosions and new bone formation. It affects 10% to 30% of patients with psoriasis, and has an estimated prevalence of approximately 1%. PsA is considered to be primarily an autoimmune disease, driven by autoreactive T cells directed against autoantigens present in the skin and in the joints. However an autoinflammatory origin has recently been proposed. Long noncoding RNAs (lncRNAs) are RNAs more than 200 nucleotides in length, that do not encode proteins. LncRNAs play important roles in several biological processes, including chromatin remodeling, transcription control and post-transcriptional processing. Several studies have shown that lncRNAs are expressed in a stage-specific or lineage-specific manner in immune cells and that have a role in the development, activation and effector functions of immune cells. LncRNAs are thought to play a role in several diseases, including autoimmune disorders. Indeed, a few lncRNAs have been identified in systemic lupus erythematosus, rheumatoid arthritis and psoriasis. Although several high throughput studies have been performed to identify lncRNAs, their biological and pathological relevance are still unknown, and most transcriptome studies in autoimmune diseases have only assessed protein-coding transcripts. No data are currently available on lncRNAs in psoriatic arthritis. Therefore, by microarray analysis, we have investigated the expression profiles of more than 50,000 human lncRNAs in blood samples from PsA patients and healthy controls using Human Clariom D Affymetrix chips, suitable to detect rare and low-expressing transcripts otherwise unnoticed by common sequencing methodologies. Network analysis identified lncRNAs targeting highly connected genes in the PsA transcriptome. Such genes are involved in molecular pathways crucial for PsA pathogenesis including immune response, glycolipid metabolism, bone remodeling, Type 1 Interferon, Wnt, and Tumor Necrosis Factor signalings. Selected lncRNAs were validated by RT-PCR in an expanded cohort of patients. Moreover, modulated genes belonging to meaningful pathways were validated by RT-PCR in PsA PBMCs and/or by ELISA in PsA sera. The findings indicate that lncRNAs are involved in PsA pathogenesis by regulating both miRNAs and genes and open new avenues for the identification of new biomarkers and therapeutical targets.